Correction of the heat loss method for calculating clothing real evaporative resistance. (August 2015) - Wang, Faming; Zhang, Chengjiao; Lu, Yehu
Abstract: In the so-called isothermal condition (i.e., T air [air temperature]= T manikin [manikin temperature]= T r [radiant temperature]), the actual energy used for moisture evaporation detected by most sweating manikins was underestimated due to the uncontrolled fabric 'skin' temperature T sk, f (i.e., T sk, f < T manikin ). Thus, it must be corrected before being used to compute the clothing real evaporative resistance. In this study, correction of the real evaporative heat loss from the wet fabric 'skin'–clothing system was proposed and experimentally validated on a 'Newton' sweating manikin. The real evaporative resistance of five clothing ensembles and the nude fabric 'skin' calculated by the corrected heat loss method was also reported and compared with that by the mass loss method. Results revealed that, depending on the types of tested clothing, different amounts of heat were drawn from the ambient environment. In general, a greater amount of heat was drawn from the ambient environment by the wet fabric 'skin'-clothing system in lower thermal insulation clothing than that in higher insulation clothing. There were no significant differences between clothing real evaporative resistances calculated by the corrected heat loss method and those by the mass loss method. It was therefore concluded that the correction method proposed in this study has been successfully validated. Highlights: The heat loss method for calculating clothing real evaporative resistance needs to be corrected. We proposed a model to correct the heat loss method and this model has been successfully validated. Depending on the clothing type, different amounts of heat were drawn from the ambient environment. We found no statistical difference between Retheat, Retmass .